Assessment of organizational models of training system of social-human sciences in Vietnam - Dinh, Tran Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Actually many universities of social-human sciences give the important role to the development by the model of combined training and scientific research activities. Some public universities define their clear objectives to become research universities and get the regional level. This report is to present studies, analysis and assessment of strong sides and shortages of the organizational model of training system of social-human sciences in Vietnam during the recent time. Then the recommendations will be proposed for renovation of this system in the future time. Code: 11040802